2020
DOI: 10.2196/19810
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Context–Aware Biomedical Text Summarization Using Deep Neural Network: Model Development and Validation

Abstract: Background Automatic text summarization (ATS) enables users to retrieve meaningful evidence from big data of biomedical repositories to make complex clinical decisions. Deep neural and recurrent networks outperform traditional machine-learning techniques in areas of natural language processing and computer vision; however, they are yet to be explored in the ATS domain, particularly for medical text summarization. Objective Traditional approaches in ATS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…Afzal et al proposed using deep neural network model for the summarization of biomedical texts. The objective of the work was to verify the performance of deep neural networks and recurrent networks in the field of ATS since these are previously known to outperform machine learning models in NLP tasks [25]. The results of these experiments indeed indicated that the deep neural network models performance showed greater accuracy.…”
Section: Related Workmentioning
confidence: 97%
“…Afzal et al proposed using deep neural network model for the summarization of biomedical texts. The objective of the work was to verify the performance of deep neural networks and recurrent networks in the field of ATS since these are previously known to outperform machine learning models in NLP tasks [25]. The results of these experiments indeed indicated that the deep neural network models performance showed greater accuracy.…”
Section: Related Workmentioning
confidence: 97%
“…Additionally, the application of text summarization can be extended and customized to the needs of different specialties, training machine learning algorithms on critical areas of focus in prior documentation relevant to a particular clinical field. 8,10,11 NLP is a currently available form of technology that can be utilized to discover previously missed or improperly coded patient conditions including hierarchical condition category codes. 6,7 However, improperly coded information could also be a limitation, relying on incorrect inputs that result in inappropriate decisions which are perpetuated over time.…”
Section: Clinical Documentationmentioning
confidence: 99%
“…20 Studies on text summarization have demonstrated its utility in clinical information extraction and may serve as a potential decision support aid. 8,23 NLP could be applied to extract information from clinical encounters for text summarization and offer clinical decision support by helping identify a correct diagnosis. 8,23…”
Section: Clinical Decision Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts in summarization have focused on neural methods (See et al, 2017;Gehrmann et al, 2018) using benchmark datasets compiled from news articles, such as the CNN-DailyMail dataset (CNN-DM) (Hermann et al, 2015). However, despite its importance, fewer efforts have tackled text summarization in the biomedical domain for both consumer and clinical text and its applications in Question Answering (QA) (Afantenos et al, 2005;Mishra et al, 2014;Afzal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%